Implementasi Pendidikan Inklusif untuk Mendukung Kesejahteraan Anak Berkebutuhan Khusus di Lingkungan Sekolah - Roudlotun Najwa Khoiriyah; Risbon Sianturi; Taopik Rahman; Aisyah Maelani Sopian; Zahra Kafa Rizna (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to analyze the implementation of inclusive education in supporting the welfare of children with special needs in the school environment. The method used is the literature study method, namely a research approach carried out through an in-depth review of various scientific sources relevant to the study topic. The results of the study indicate that the implementation of inclusive education has a positive impact on the social, emotional, and academic development of children with special needs, although there are still obstacles such as limited facilities, lack of teacher training, and minimal support from the school environment. The discussion shows that the success of inclusive education is greatly influenced by collaboration between teachers, parents, and schools in creating a friendly and adaptive learning environment. In conclusion, the implementation of inclusive education plays an important role in improving the welfare of children with special needs, so there is a need for improved service quality, supportive policies, and ongoing training for educators